UPAYA PENCEGAHAN HULU HILIR STUNTING DI WILAYAH KEDUNGWUNI BARAT - Fitriyani, Nur Lu’lu; Khasanah, Marekhatun; Najati, Tiara Izza; Rohmaniyah, Maghfirotur; Maulidiya, Nur; Fahreza, M. Nahrul (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Stunting is short or very short based on length or height according to age which is less than -2 standard deviation (SD) on the WHO growth curve which occurs due to irreversible conditions due to inadequate nutritional intake and/or recurrent infections / chronic disease that occurs within 1000 HPK. Malnutrition occurs when the baby is in the womb and in the early stages of life after birth, but only appears after the child is 2 years old (Izwardy, 2019). This upstream-downstream effort to prevent stunting in the West Kedungwuni region was carried out for approximately 2 months from 11 July to 26 September 2023. This effort consists of 3 stages, namely the preparation, implementation and evaluation stages. Stunting cannot be treated but can be prevented. The Indonesian government has established a policy that efforts to prevent stunting are carried out through specific nutritional interventions and sensitive nutritional interventions. Specific nutritional interventions are interventions that focus on the health sector and contribute 30% to solving the stunting problem. Sensitive nutritional interventions focus on outside the health sector and contribute by 70% to solve the problem of stunting. Stunting is caused by several factors such as: low maternal knowledge, inappropriate parenting patterns, poor nutritional status, LBW, and low family economic status have a significant relationship to the incidence of stunting in children. Stunting cannot be treated but can still be prevented, several things that can be done to prevent stunting are maintaining nutritional intake at 1000 HPK (First Day of Life).